Sinicizing Christianity - Zheng, Yangwen. (Studies in Christian Mission, 2017)
Chinese people have been instrumental in indigenizing Christianity. Sinizing Christianity examines Christianity's transplantation to and transformation in China by focusing on three key elements: Chinese agents of introduction; Chinese redefinition of Christianity for the local context; and Chinese institutions and practices that emerged and enabled indigenisation. As a matter of fact, Christianity is not an exception, but just one of many foreign ideas and religions, which China has absorbed since the formation of the Middle Kingdom, Buddhism and Islam are great examples. Few scholars of China have analysed and synthesised the process to determine whether there is a pattern to the ways in which Chinese people have redefined foreign imports for local use and what insight Christianity has to offer. Contributors are: Robert Entenmann, Christopher Sneller, Yuqin Huang, Wai Luen Kwok, Thomas Harvey, Monica Romano, Thomas Coomans, Chris White, Dennis Ng, Ruiwen Chen and Richard Madsen.